A Service for ClinicSpace Architecture to Provide Context Data Persistence and Context-Based Selection of Documents - Maran, Vinícius; Augustin, Iara; Saccol, Deise de Brum (Anais do Seminário Integrado de Software e Hardware (SEMISH); 2012: Anais do XXXIX Seminário Integrado de Software e Hardware, 2012)
Actual healthcare systems suffer from a high rate of rejection by the physicians who use these systems, because it is necessary that the users explicitly provide information constantly to these systems. So, one of the biggest challenges for pervasive healthcare systems is to find how use the environment context information in a simple and functional way between different computer systems. In the literature, ontologies are frequently used for the representation of context and have an important role in pervasive systems if used together with persistence and retrieval of context information. For proposing a solution to the mentioned problems, is under development an architecture called ClinicSpace which focuses on providing assistance to physicians in performing their daily tasks, using concepts defined in ubiquitous computing, which allows the system adapt itself constantly to the user and their needs. This work describes the process of developing an integrated service to ClinicSpace architecture, which supports the use of context data and clinical documents in a distributed manner, and also allows the contextualized selection of clinical documents, using data from the context at the moment of clinical information query.